2010
DOI: 10.1016/j.virol.2010.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the putative pipo of soybean mosaic virus suggests disruption of PIPO protein impedes movement

Abstract: The presence of a small open reading frame embedded in the P3 cistron of potyvirus turnip mosaic virus, termed "pipo," was recently discovered. We have now studied the putative pipo of soybean mosaic virus (SMV). Introduction of single, or multiple, stop codon mutations at different locations within pipo, without substitution in polyprotein amino acids, did not abolish replication, but restricted the virus to small cluster of cells within the inoculated leaves. Furthermore, extensive mutagenesis of the conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 18 publications
4
80
0
Order By: Relevance
“…Furthermore, potyvirus P3 localizes to PD and acts in intercellular virus movement (Wei et al, 2010;Wen and Hajimorad, 2010). These reports are consistent with our finding that NbRbCS interacts with MPs of ToMV and TMV, which are involved in viral cell-to-cell movement.…”
Section: Role Of Rbcs In Virus Movementsupporting
confidence: 91%
“…Furthermore, potyvirus P3 localizes to PD and acts in intercellular virus movement (Wei et al, 2010;Wen and Hajimorad, 2010). These reports are consistent with our finding that NbRbCS interacts with MPs of ToMV and TMV, which are involved in viral cell-to-cell movement.…”
Section: Role Of Rbcs In Virus Movementsupporting
confidence: 91%
“…This polypeptide is only produced by a very small fraction of the viral RNA, which contains the single nucleotide insertion (Olspert et al, 2015). P3N-PIPO contributes to cell-to-cell movement of the virus in susceptible hosts (Chung et al, 2008;Wen and Hajimorad, 2010). HC-Pro, along with P3 and Cl, regulates SMV virulence Hajimorad et al, 2008;Seo et al, 2009;Zhang et al, 2009;Hajimorad et al, 2011;Seo et al, 2011;Chowda-Reddy et al, 2011;Wen et al, 2011).…”
mentioning
confidence: 99%
“…Recently, a bioinformatic approach revealed that an 11th protein, PIPO (pretty interesting Potyviridae ORF), is translated from a ϩ2 frame (5). The first study investigating the functions of this protein revealed its role in virus movement (56). Most of the potyviral proteins are shown to have multiple functions, and the viral genome-linked protein (VPg) is one of the most versatile of them.…”
mentioning
confidence: 99%